Treating Homosexuality: A Response to Yarhouse - Howsepian, A. A. (Christian bioethics, 2004)
Professor Mark A. Yarhouse proposes an ‘identity synthesis’ model of sexual modification therapy for homosexuals. This model is meant primarily to target the process by which one's sexual identity is synthesized, rather than the changing of sexual orientation itself. I highlight some of the advantages of Yarhouse's model along with some of its potential pitfalls. My primary point of departure with Yarhouse concerns how one ought to direct those selfidentified homosexual clients who fall within our clinical sphere of influence and who, in the end, contrary to our better judgment, decide that they would like to pursue a course of “homosexualization.” Based on the “autonomy”- emphasizing aspects of the identity synthesis model, it appears that Yarhouse is willing to sanction the referral of certain clients to “therapists” who are willing to facilitate these clients' homosexualization. I do not believe that Christians involved in the care of homosexuals can licitly participate in such referrals.